Ethnoscience Studies in Making of Bale Adat: Literature Review - M. Khairul Wazni; Agus Muliadi; M. Yamin (Postgraduate, University of Mataram, 2023)
This study aims to elaborate on indigenous science contained in the use of materials for making bale adat based on scientific concepts. This study is a literature study with data sources from previous research articles that have topics related to ethnoscience learning, indigenous science in the tradition of materials for making bale adat, and the potential for integration of indigenous science in learning natural sciences. The procedure in literature study research is carried out in stages, namely collecting library data, reading, taking notes, studying, collecting concepts or manuscripts, then carrying out elaboration and explanation of the collected data/text. The study results show that (1) bale adat typical of the Sasak tribe consists of several types, namely bale beleq bencingah, bale bonter, bale tani, bale jajar, bale tajuk, berugag (sekepat-sekenam); (2) Indigenous science in the materials for making bale adat, namely: a) the foundation for bale adat is made from a mixture of clay, tree sap, straw ash or rice husk, and buffalo dung mixed with water, b) floor of bale adat periodically smeared with buffalo dung mixed with water to reduce humidity, c) the walls of bale adat or room covering are made of woven bamboo slats known as the local term pager, d) woven pagers are made of ampel bamboo with various motifs and sometimes to beautify the pager , the material used is spotted bamboo which has colorful bark, d) teken, ampak, lampen, and langkar used in the bale adat are made from the part of the tree that is believed to be the strongest or known locally as kayu galih, e) roof made of weeds leaves woven into bamboo frame clips which are split into small pieces; (3) indigenous science in the materials for making bale adat can be integrated into the school science learning concept, namely in the material: a) material on network structure and function, as well as technology inspired by plant structure , b) material properties and utilization of materials in everyday life.